(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Who has the power in Rome? The municipal administration does not have it. The regional administration does not have it, let alone the State. What are the real powers in Rome? They are no longer even the builders, they were in the post-war period, it was the time that can be defined as “Real Estate” where there was a relationship of dependence between the real estate company and the municipal administrations. But today the builders are no longer even the masters of Rome. Today the masters of Rome are really many, they are a caste that is not at all the political caste, it is a caste of the Grand commis of State, the great directors of the ministries, the great secretaries of the corporative associations and all that revolves around them. Those are the ones who hold Rome. Faced with this situation, I do not intend to speak of Rome around the Grande Raccordo Anulare, but of Rome in the historic center. A strong hand would be necessary for the historic center. I do not believe that the Casamonica and the Carminati, which are a very serious problem, are the basic problem of the administration of Rome, which concerns all sectors.